The Effect of Increasing Compensation on Employee Work Motivation in Multi-Business Cooperatives Prima Grathia Prosperous Lombok - Sariman, Angelina; Lukitasari, Diah; Dianti, Ira (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The purpose of this research is to determine the effect of providing compensation on employee work motivation at the Prima Grathia Sejahtera Lombok Multi-Enterprise Cooperative. This research used quantitative methods with a sample size of 54 people. The research methods used are coefficient of determination and multiple linear regression. The results in this study prove that work compensation has a partially positive and significant effect on employee performance because the t-count of 4,933 is greater than the t-table of 2,009. Work motivation has a partially positive and significant effect on employees because the t-count is 4,933 and the t-count of 755 is greater. from t-table 2.009. Meanwhile, simultaneously the compensation variable has a positive and significant effect on employee motivation because the f-count value of 570 is greater than the f-table of 2.56.